The Correlation of Students' Reading Motivation, Vocabulary Mastery, and Reading Comprehension Ability - Siska Wulandari (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: Reading is one of the important skills in English because it can help students to get more knowledge. In comprehend a reading text, readers need to have a lot of vocabularies. Vocabulary is the main key in understanding reading. Vocabulary knowledge is one of the best predictors of learners’ ability in reading comprehension. To have a good reading comprehension, readers also need motivation. Motivation is a very big desire that might come internally or externally from individuals or from other people. The aim of this study is to find out the correlation between reading motivation, vocabulary mastery and reading comprehension. To investigate there is correlation between three variables, researcher uses correlation research. The population of this research was the students in the fourth semester of English Department at University of Islam Malang in Academic year 2020/2021. The respondent of the research were 60 students from the total two classes. The instruments that used by the researcher were questionnaire and tests of vocabulary and reading comprehension. The questionnaire was used to gather information about students' reading motivation. Then the tests were used to measure students' vocabulary mastery and reading comprehension ability. In analyzing the data, researcher used SPSS 20.0. The result showed that the mean score reading motivation was 74.02 by standard deviation was 10.432. The data reveals that mean score of vocabulary mastery was 75.45 by standard deviation was 8.276 and 73.17 was the mean score of reading comprehension by standard deviation was 9.140. Also, insignificant value was found 0.000. It means that the significant value was lower than 0.05. In other word, the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) rejected. So, it can be concluded that there is significant correlation between students’ reading motivation, vocabulary mastery and reading comprehension. Based on the results of the research, it is aimed at lecturers being able to direct students to be diligent in reading books during the learning process and teachers to motivate students continuously on the importance of reading. Students' vocabulary mastery should be improved and students can read more texts because reading can add new vocabulary for students. In addition, the vocabulary obtained must be directly practiced in reading so that it can help students increase vocabulary. Then, conduct a similar study with non-EFL subjects by the future researcher.Keywords: Correlation, Students’ Motivation, Vocabulary Mastery, Reading Comprehension Ability